1982
DOI: 10.1002/chin.198217204
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: PREPARATION OF SOME 1,2,3,4‐TETRAZOLES

Abstract: Die Umsetzung der Thiosemicarbazide (I) mit salpetriger Säure (II) ergibt die Thiatriazole (III), die unter basischen Bedindungen zu den entsprechenden Tetrazolthiolen (IV) isomerisieren.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…On the other hand, five‐membered heterocyclic compounds, natural as well as synthetic, are important for their biological activities. Compounds with thiatriazole rings are of interest due to their broad spectrum of biological activities, such as antihypertensive 7, antibacterial 8, antifungal 9, antitubercular 10, fungicidal 11, and anticancer activities 12. Further, it has been reported that many biologically active natural and synthetic products have interesting molecular symmetry 13.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, five‐membered heterocyclic compounds, natural as well as synthetic, are important for their biological activities. Compounds with thiatriazole rings are of interest due to their broad spectrum of biological activities, such as antihypertensive 7, antibacterial 8, antifungal 9, antitubercular 10, fungicidal 11, and anticancer activities 12. Further, it has been reported that many biologically active natural and synthetic products have interesting molecular symmetry 13.…”
Section: Introductionmentioning
confidence: 99%
“…1 Several Palladium (II) complexes having thioamide ligands are reported to be potential antitumor activity [2][3] and significant antifungal activity 4 . Cowper and Co-workers 5 have examined the antimicrobial activity of some 1,2,3,4-Tetrazole having thioamide group. The present paper aims at structural and biological evaluation of some Palladium (II) complexes ligated by 1-substituted phenyl-tetrazoline-5-thione.…”
Section: Introductionmentioning
confidence: 99%
“…2 For example, mono-substituted aminothiatriazoles (4 in Scheme 1) exhibit a wide range of interesting biological properties, including antihypertensive, 3 antibacterial, 4 antitubercular, 5 antiviral, 6 fungicidal, 7 anticancer, 8 central nervous system stimulant, and muscle relaxant activities. 9 Among currently available synthetic routes to mono-substituted aminothiatriazoles, the most widely used one is based upon the method outlined originally by Freund and his co-workers, 10 which involves the treatment of thiosemicarbazides with nitrous acid.…”
mentioning
confidence: 99%